2017
DOI: 10.14486/intjscs657
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Correlation between Self-esteem in Decision-making and Decision-making Styles of Football Referees in terms of their Refereeing Experience and Violence Perceptions

Abstract: The study was conducted in order to determine self-esteem in decision-making and decisionmaking styles of football referees in terms of their experience and violence perceptions and to examine the correlation between their self-esteem in decision-making and decision-making styles. The population of the study was composed 1080 referees who were assigned to the matches of the 7 th region where there were 8 provinces under Turkish Football Federation during 2014-2015 football season. The sample of the study was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…In contrast, BP is more significantly correlated with anxiety, where the fear of being blamed is avoided by passing on the responsibility to another individual for making decisions. [ 26 ] The VG style, which is not a feature of the clinical population, was not seen even among the HCs in the current study. This might be attributed to findings that the two groups did not differ on positive beliefs about worry, a type of dysfunctional metacognitive belief that is also related to defensive DM[ 34 39 ] and is seen in people at risk.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…In contrast, BP is more significantly correlated with anxiety, where the fear of being blamed is avoided by passing on the responsibility to another individual for making decisions. [ 26 ] The VG style, which is not a feature of the clinical population, was not seen even among the HCs in the current study. This might be attributed to findings that the two groups did not differ on positive beliefs about worry, a type of dysfunctional metacognitive belief that is also related to defensive DM[ 34 39 ] and is seen in people at risk.…”
Section: Discussioncontrasting
confidence: 59%
“…[ 25 ] The non-vigilant styles of DM are also connected with low self-esteem and considered defensive avoidance where an individual chooses either PR to avoid failure or BP to avoid blame for bad consequences. [ 26 ] The RDD sample was also found to have significantly higher metacognitive dysfunctional beliefs than HC. The results of the studies have shown that the clinical sample got elevated scores on dysfunctional metacognitive beliefs with significant differences in domains, namely negative beliefs about uncontrollability and danger of worry, cognitive confidence, and need for control, as observed in the findings of the current study as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Baştuğ et al (2016) found that the self-confidence of soccer referees increased and their decision-making skills increased. Gülle et al (2017) concluded that among the referees of soccer, those who were more experienced and those who were not exposed to violence had higher self-esteem in their decision-making levels.…”
Section: Discussionmentioning
confidence: 99%
“…The decisions made by a referee must consider the fairness, sportsmanship, objectivity, and consistency aspects. Football referees generally have a high self-esteem in making decisions and the decision-making styles are used more effectively (Gülle, 2017).…”
Section: Introductionmentioning
confidence: 99%